Analysis of Factors Affecting Purchase Intention of Chinese Steel and Iron Products in Batam - Fernado Fernado; Erilia Kesumahati (Universitas Batanghari Jambi, 2023)
This study aims to determine the cause of the high purchase intention of imported Chinese steel and iron products in Batam City. Iron and steel products are one of the highest imported category on 2020 that leads the main reason for this study. The collection of questionnaires was carried out using Google Form filled out by 211 building shop owners or managers. The data processing tool used in this study is SPSS version 26.0.0 with data quality test, classical assumption tests, and multiple linear analysis. The results of this study are subjective norms and perceived behavioral control have a significant positive effect on purchase intention of Chinese steel and iron products.